ASPEN Lipid Injectable Emulsion Safety Recommendations, Part 1: Background and Adult Considerations. (27th May 2020) - Mirtallo, Jay M.; Ayers, Phil; Boullata, Joseph; Gura, Kathleen M.; Plogsted, Steven; Anderson, Collin R.; Worthington, Patricia; Seres, David S.; Nicolai, Emily; Alsharhan, Mohammad; Gutsul, Liliia; Mason, Angelina E.
Abstract: Lipid injectable emulsions (ILEs) are complex pharmaceutical formulations used as a source of energy and essential fatty acids in parenteral nutrition. Issues associated with ILE use are distinctly different from oral fat and arise from emulsion stability, dose, and infusion tolerance. Since 1975, soybean oil has been the consistent source oil used in ILE formulations in the US. Partly because of safety concerns with the soybean‐based ILE and frequent and long‐standing problems with product inventory shortages, new ILE products have become available. Gaps in ILE best practices create a risk for ILE safety errors in prescribing, compounding, and administration of these products. This paper provides information on appropriate indications, dosing, and methods to avoid potential errors with ILE products in the US. This paper (Part 1) will focus on ILE background, information, and recommendations for adult patients, whereas Part 2 of this series will focus on neonatal and pediatric patient–specific information.